Studi Komparatif ISR dan GRI Pada Emiten Syariah Sektor Pertanian dan Pertambangan yang Terdaftar di BEI Tahun 2020-2021 - Elyanti Rosmanidar; Azra Elindra; Laily Ifazah (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2023)
Disclosure of social responsibility can be disclosed in the company’s annual report or sustainable report. Disclosure of corporate social responsibility can be measured using the GRI Index or ISR Index. This study aims to determine the comparison of social responsibility disclosure in each aspect based on the GRI Index with the ISR Index which is considered to be more representative of social responsibility disclosure in sharia entities. This study uses secondary data in the form of annual reports obtained from the website of each company that is the research sample. The number of samples in this study is 36 annual reports from 18 companies with sharia shares in the agricultural and mining sectors listed on the Indonesia Stock Exchange for 2020-2021. The analytical techniques used in this study are scoring, descriptive statistics, classical assumption test and independent sample t test. The result of the study show that the investment and financial aspects, products and services, social, and environmental aspects based on the ISR Index are better than the GRI Index. Meanwhile, the aspects of labor and corporate governance based on the GRI Index are better than the ISR Index, and the measurement of social responsibility as a whole shows that disclosure with the GRI Index is better than the ISR Index.